2022
DOI: 10.1021/acs.orglett.2c00227
|View full text |Cite
|
Sign up to set email alerts
|

Pyridazine N-Oxides as Photoactivatable Surrogates for Reactive Oxygen Species

Abstract: A method for the photoinduced evolution of atomic oxygen from pyridazine N-oxides was developed. This underexplored oxygen allotrope mediates arene C–H oxidation within complex, polyfunctional molecules. A water-soluble pyridazine N-oxide was also developed and shown to promote photoinduced DNA cleavage in aqueous solution. Taken together, these studies highlight the utility of pyridazine N-oxides as photoactivatable O­(3P) precursors for applications in organic synthesis and chemical biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.24–8.17 (m, 4H), 7.95 (s, 2H), 7.58 (dddt, J = 9.8, 8.7, 5.4, 1.3 Hz, 6H). The 1 H NMR data exactly matches the previously reported data …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.24–8.17 (m, 4H), 7.95 (s, 2H), 7.58 (dddt, J = 9.8, 8.7, 5.4, 1.3 Hz, 6H). The 1 H NMR data exactly matches the previously reported data …”
Section: Methodsmentioning
confidence: 99%
“…The 1 H NMR data exactly matches the previously reported data. 54 3,6-Bis(methylthio)pyridazine (19). A solution of 9b 33 (8.7 mg, 0.05 mmol) in HFIP (0.5 mL) was treated with 2,5-norbornadiene (2, 18.4 mg, 21 μL, 0.2 mmol), and the reaction mixture was stirred at 60 °C (oil bath) for 17.5 h. The solution was concentrated under vacuum, and the residue was purified by PTLC (33% EtOAc− hexanes) to afford 18 (7.6 mg, 88%) as a white solid.…”
Section: Cycloaddition Of N-sulfonyl-1-aza-13-butadienesmentioning
confidence: 99%
“…On the one hand, the cyclization of PD-ring (strategy I) could be achieved by several methods, such as the Schiff-base condensation between hydrazine and diketones 122 /anhydrides 73 /aromatic ortho-diesters, 6 oxidative N-N coupling cyclization between hydroxylamine and dinitrogen tetroxide (N 2 O 4 ), 123 or t-BuOCl and aromatic diamines, 78 Diels-Alder cycloaddition between tetrazines and substituted acetylenes [124][125][126] or ethylenes, 57,127 [3+n] cycloaddition from azomethine ylides, 128 diazo-based cycloaddition 48,104 or quarternizative cyclization, 102 and photoactivation of pyridazine-N-Oxides (PD-N-Oxides). 129 On the other hand, the modification of PD-ring (strategy II) could be achieved by a huge number of C-C or C-N coupling or cyclization methods, including Suzuki reaction, Stille reaction, nucleophilic substitution, Sonogashira reaction, Aldol condensation, C-H activated direct arylation, Minisci reaction, Ullmann reaction, Buchwald-Hartwig reaction, and aroylation via wet chemistry, thermochemistry, photochemistry, and/or electrochemistry, which have been significantly investigated and/or summarized. 53,104,130 Ritchie and collaborators 131 found that the replacement of -CHQ by -NQ (Fig.…”
Section: Synthetic Strategy and Electronic Structuresmentioning
confidence: 99%
“…The reactivity of O radicals (oxygen atoms) in solution remains underexplored [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. One of the reasons is the lack of a clean and mild method for the generation of O radicals in solution [ 1 , 2 , 3 , 4 , 9 ]. The generation of O radicals in solutions is commonly by UV irradiation of dibenzothiophene S-oxide (DBTO) [ 2 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of O radicals (oxygen atoms) in solution remains underexplored [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. One of the reasons is the lack of a clean and mild method for the generation of O radicals in solution [1][2][3][4]9]. The generation of O radicals in solutions is commonly by UV irradiation of dibenzothiophene S-oxide (DBTO) [2,9,13].…”
Section: Introductionmentioning
confidence: 99%